Presumed and definite bacteremia in extremely low gestational age newborns - Patel, Sonal (2010)
AIM: To explore risk patterns for presumed and definite, early and late neonatal bacteremia. METHODS: We studied 1106 ELGANs who survived until postnatal day 28. We defined early definite bacteremia as a positive bacterial culture in the first week and definite late bacteremia as a positive bacterial culture in week 2, 3 or 4. Bacteremia was presumed if antibiotics were given for more than 72 hours despite negative blood cultures. RESULTS: Risk patterns did not differ much for presumed and definite bacteremia in the first postnatal month. While maternal and pregnancy characteristics were associated with early bacteremia, neonatal co-morbidities, especially NEC, were the main antecedents/correlates of late bacteremia. All four categories of bacteremia were associated with younger gestational age and lower birth weight. Infants with presumed and definite bacteremia had similar distributions of days of ventilation and oxygenation. CONCLUSION: Definite and presumed late bacteremia have rather similar risk patterns, while those of early and late bacteremia differ appreciably.